Matriks Copson dan Ruang Barisan - Salwa, Salwa; Irwansyah, Irwansyah; Yumni Awanis, Zata; Abdurahim, Abdurahim; Robbaniyyah, Nuzla Af'idatur (Mandalika Mathematics and Educations Journal, 2025)
Sequence spaces are one of the topics in the field functional analysis such as null sequence space, converging sequence space and bounded sequence space designated and respectively. Those sequence spaces are normed spaces. Entry of Copson matrices denoted by with value and 0 for other . Null sequence space, , converging sequence space and bounded sequence space with Copson matrices built new sequence spaces that are squence spaces . The purpose of this study is to get some properties that occur to those sequence spaces with the same normed as sequence space . The results of this study are sequence spaces are Banach spaces with mapping coordinate is continues (BK), there are inclusion properties on sequence spaces, sequence space has AK property and sequence spaces and are compact.